Elevated levels of IL-6 and IGFBP-1 predict low serum IGF-1 levels during continuous infusion of rhIGF-1/rhIGFBP-3 in extremely preterm infants. (February 2020) - Klevebro, Susanna; Hellgren, Gunnel; Hansen-Pupp, Ingrid; Wackernagel, Dirk; Hallberg, Boubou; Borg, Jan; Pivodic, Aldina; Smith, Lois; Ley, David; Hellström, Ann
Abstract: Objective: Steady state insulin-like growth factor-1 (IGF-1) levels vary significantly during continuous intravenous infusion of recombinant human insulin-like growth factor-1/recombinant human insulin-like growth factor binding protein-3 (rhIGF-1/rhIGFBP-3) in the first weeks of life in extremely preterm infants. We evaluated interleukin-6 (IL-6) and insulin-like growth factor binding protein-1 (IGFBP-1) levels as predictors of low IGF-1 levels. Methods: Nineteen extremely preterm infants were enrolled in a trial, 9 received rhIGF-1/rhIGFBP-3 and 10 received standard neonatal care. Blood samples were analyzed daily for IGF-1, IL-6 and IGFBP-1 during intervention with rhIGF-1/rhIGFBP-3. Results: Thirty seven percent of IGF-1 values during active treatment were <20 μg/L. Among treated infants, higher levels of IL-6, one and two days before sampled IGF-1, were associated with IGF-1 < 20 μg/L, gestational age adjusted OR 1.30 (95% CI 1.03–1.63), p = .026, and 1.57 (95% CI 1.26–1.97), p < .001 respectively. Higher levels of IGFBP-1 one day before sampled IGF-1 was also associated with IGF-1 < 20 μg/L, gestational age adjusted OR 1.74 (95% CI 1.19–2.53), p = .004. Conclusion: In preterm infants receiving continuous infusion of rhIGF-1/rhIGFBP-3, higher levels of IL-6 and IGFBP-1 preceded lower levels of circulating IGF-1. These findings demonstrate a need to further evaluate if inflammation and/or infection suppress serum IGF-1 levels. The trial is registered at ClinicalTrials.gov (NCT01096784). Highlights: IGF-1 levels vary during rhIGF-1/rhIGFBP-3 treatment in preterm infants. High IL-6 and IGFBP-1 levels predicted low serum IGF-1 < 20 μg/L. The results suggest that inflammation and/or infection may suppress serum IGF-1. This finding increases the understanding of the feasibility of rhIGF-1/rhIGFBP-3 treatment.